THE EFFECTIVENESS OF ORGANIC FERTILIZER AND MICORIZA ARBUSCULA ON GROWTH AND PRODUCTIVITY GREEN EGGPLANT (SOLANUM MELONGENA L.) - Diah Sudiarti (Hasanuddin University, 2021)
Green eggplant (Solanum melongena L.) is a food plant grown for its fruit. The fruit of the eggplant depends on the fruit stalk and is a single true fruit, thick, soft, and juicy. This study was a completely randomized design with a three-treatment pattern. The first is a combination of organic fertilizer and arbuscular mycorrhizal fungi, the second is a positive control, namely using NPK fertilizer, the third is a negative control, namely without treatment. Each treatment was repeated three times and each repetition consisted of 3 plants. Plant growth parameters consist of plant height and number of leaves. Plant productivity parameters consist of the number of fruit, fruit wet weight, and dry weight. Based on the results of the study, it was obtained data that the combination of organic fertilizer and Arbuscular Mycorrhizal Fungi had better growth and productivity results compared to other treatments with an average plant height of 44.46; the average number of leaves 11.12; the average number of fruits was 5.51; mean fruit wet weight 106; and the average dry weight of fruit 84. The results of the Anova statistical test showed that the significance value of plant height and a number leaves was 0.000 (α <0.05), and the significance value for the number of fruits was 0.006 (α <0.05), while the significance value of weight wet and dry weight of fruit is 0.000 (α <0.05), this indicates that the combination of organic fertilizer and Arbuscular Mycorrhizal has a significant effect on the growth and productivity of green eggplant plants.